1997
DOI: 10.1063/1.474836
|View full text |Cite
|
Sign up to set email alerts
|

Langmuir monolayers as disordered solids: Strain-state calculations applied to stearic acid

Abstract: This paper presents a calculational procedure to determine the equilibrium phase for a given surface pressure . The monolayer is treated as orientationally free tails grafted to a two-dimensional net formed by the head groups of the amphiphilic molecules. The head groups form a subsystem with translational degrees of freedom characterized by strain variables in the plane of the surface, and the tail groups compose a subsystem characterized by rotational degrees of freedom. The order in the monolayer derives in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

1999
1999
2003
2003

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 24 publications
(44 reference statements)
1
13
0
Order By: Relevance
“…6 In recent elegant studies of the shear elasticity of monolayers, 7,8 it has been confirmed that these phases are more crystalline in nature, rather than hexatic. These findings strongly support our previously introduced model of Langmuir monolayers as disordered solids, 3,9 as do other studies 10,11 that demonstrate mesophases can be treated as two-dimensional ͑2D͒ solids.…”
Section: Introductionsupporting
confidence: 80%
See 3 more Smart Citations
“…6 In recent elegant studies of the shear elasticity of monolayers, 7,8 it has been confirmed that these phases are more crystalline in nature, rather than hexatic. These findings strongly support our previously introduced model of Langmuir monolayers as disordered solids, 3,9 as do other studies 10,11 that demonstrate mesophases can be treated as two-dimensional ͑2D͒ solids.…”
Section: Introductionsupporting
confidence: 80%
“…The results of this study further support the generality, efficacy, and usefulness of our model that treats mesophases of Langmuir monolayers as disordered solids. In this, as well as earlier treatments, 3,10,11 we have endeavored to show how the elastic solid theory of Langmuir monolayers is a natural, easily extended approach that offers a completely consistent and unifying structure for understanding a wide variety of experimental findings for Langmuir monolayers. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We shall, following our previous suggestions 3 and other work, advocate the concept of Langmuir monolayers as disordered solids. 6 Theoretical attempts to describe the symmetries of the phases in the generic (-T) phase diagram attack the problem from two opposite viewpoints: liquid-crystalline or solid state. But it is always the hexagonal, high-pressure ͑LS͒ phase which serves as the highest symmetry, parent phase.…”
Section: Introductionmentioning
confidence: 99%